2002
DOI: 10.1128/aac.46.8.2373-2380.2002
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Toxicology Studies of 1263W94, a Potent and Selective Inhibitor of Human Cytomegalovirus Replication

Abstract: 1263W94 is a novel benzimidazole compound being developed for treatment of human cytomegalovirus infection. No adverse pharmacological effects were demonstrated in safety pharmacology studies with 1263W94. The minimal-effect dose in a 1-month rat study was 100 mg/kg/day, and the no-effect dose in a 1-month monkey study was 180 mg/kg/day. Toxic effects were limited to increases in liver weights, neutrophils, and monocytes at higher doses in female rats. 1263W94 was not genotoxic in the Ames or micronucleus assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
72
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 20 publications
1
72
1
Order By: Relevance
“…Unlike TCRB, it is active against Epstein-Barr virus (42). Preclinical safety and pharmacokinetic studies with maribavir found it was well tolerated and established that the drug has good oral bioavailability and low toxicity compared to currently available HCMV drugs (21,25). Human studies yielded a good safety profile and established that maribavir reduced titers of HCMV in semen and urine from patients in a phase I/II clinical trial (25).…”
mentioning
confidence: 97%
“…Unlike TCRB, it is active against Epstein-Barr virus (42). Preclinical safety and pharmacokinetic studies with maribavir found it was well tolerated and established that the drug has good oral bioavailability and low toxicity compared to currently available HCMV drugs (21,25). Human studies yielded a good safety profile and established that maribavir reduced titers of HCMV in semen and urine from patients in a phase I/II clinical trial (25).…”
mentioning
confidence: 97%
“…1263W94 has been shown to have minimal cytotoxicity against bone marrow progenitors and various human leukemic cell lines in vitro (1,2) and limited toxicity in rats and monkeys (6). 1263W94 was rapidly and well absorbed in animals, with absolute oral bioavailabilities of ϳ90% in rats and ϳ50% in monkeys (6).…”
mentioning
confidence: 99%
“…Another subset of benzimidazoles is exemplified by the L-ribose derivative maribavir (1263W94). The drug is a potent inhibitor of CMV and Epstein-Barr virus, including CMV strains resistant to currently available drugs (4,9). Maribavir has good oral bioavailability, with few limiting side effects noted in a phase I clinical trial, which showed marked reduction in CMV shedding in semen at 4 weeks in human immunodeficiency virus-infected subjects (13).…”
mentioning
confidence: 99%